2019
DOI: 10.3390/f10121110
|View full text |Cite
|
Sign up to set email alerts
|

A Mathematical Model for the Integrated Optimization of Harvest and Transport Scheduling of Forest Products

Abstract: The costs related to forest harvesting and wood transport are key to the economic viability of forest investments. These operations compose a major share of the total cost of wood production and thus need to be conducted in an efficient manner. In this paper, we propose a novel optimization model to tackle this issue and perform the daily and weekly plan of harvesting operations, in order to minimize the costs related to the machinery operation, movement, and wood transportation, subject to demand constraints.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…With the advance of new technologies and systems become easier to obtain models that meet the time demands required to solve complex problems in the industry, once is desirable fast solutions in a few hours or days. In such cases, therefore, time represents a valuable resource for companies mainly at the operational level (Santos et al, 2019). Then defi nitely, the computation time may be a limiting factor to the applicability of some optimization techniques (François et al, 2017) as observed in two functions S and S .…”
Section: Discussionmentioning
confidence: 99%
“…With the advance of new technologies and systems become easier to obtain models that meet the time demands required to solve complex problems in the industry, once is desirable fast solutions in a few hours or days. In such cases, therefore, time represents a valuable resource for companies mainly at the operational level (Santos et al, 2019). Then defi nitely, the computation time may be a limiting factor to the applicability of some optimization techniques (François et al, 2017) as observed in two functions S and S .…”
Section: Discussionmentioning
confidence: 99%
“…Optimization of the traditional forward product flows of wood is a well-researched area, with problems ranging from harvesting (Santos et al 2019;Mesquita et al 2021) through facility-level decision-making (e.g. sawmilling Maturana et al 2010), cutting pattern optimization (Koch et al 2009) to network-level modeling (Pekka et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Optimization models related to forestry operations planning have been used in recent years in several academic works, such as case studies in log transportation [3,15], harvesting and transportation [8] and strategic planning problem [6,7,12,16].…”
Section: Introductionmentioning
confidence: 99%